Genetic structure of the sea-bob shrimp (Xiphopenaeus kroyeri Heller, 1862; Decapoda, Penaeidae) along the Brazilian southeastern coast - Voloch,Carolina Moreira (2005)
The sea-bob shrimp, Xiphopenaeus kroyeri, is one of the most important economic marine resources along the entire Brazilian coast. Nevertheless, despite its economic importance, no studies have examined the population genetics of this species. In this paper, we used ten allozyme loci to study the pattern of genetic structuring in X. kroyeri along the southeastern Brazilian coast. Seven of the ten analyzed loci were polymorphic, yielding observed heterozygosity values higher than those reported for other penaeid shrimps. The population from São Paulo was significantly different from the other two populations (Rio de Janeiro and Espírito Santo), which, in turn, seem to form a single panmitic unit. Therefore, our results clearly indicate that conservation policies for this species should consider the São Paulo population as an independent stock from those of Rio de Janeiro and Espírito Santo.